Counseling on the Prevention of Early Marriage in Adolescents at Smpn 5 Praya Timur - Rejeki, Sri; Utama, Andi Putra; Asri, Yasir; Efendi, Muh.Ruslan; Nufus, Hayatu; Hadijah, St. (Abdi Masyarakat, 2024)
Child marriage among teenagers has become a serious social issue, particularly in Central Lombok Regency. This phenomenon shows a tendency for teenagers to opt for marriage at a young age rather than continuing their education, which brings negative impacts on health, education, and socio-economic welfare. According to data from BKKBN NTB, in 2015, West Nusa Tenggara had the second-highest rate of child marriage in Indonesia, with a percentage of 5.81%. Despite government regulations aimed at preventing early marriage, their implementation has been less than optimal. SMP Negeri 5 Praya Timur, located in Beleke Lebe Sane Village, East Praya District, Central Lombok Regency, faces this issue directly, with many students deciding to leave school to marry at an early age. A lack of understanding regarding the negative impacts of early marriage, particularly related to reproductive health and education, is one of the primary causes of this phenomenon. The community service activity conducted at SMP Negeri 5 Praya Timur aimed to provide comprehensive counseling to students about the dangers of early marriage and the importance of continuing education to higher levels. The method used was Participatory Action Research (PAR), which involved active participation of students in understanding issues related to early marriage. This counseling was expected to raise student awareness about the risks of early marriage and motivate them to pursue further education. The results of this activity showed an increase in students' understanding of the negative impacts of early marriage and the importance of education as a path to a better future.